2024
DOI: 10.1186/s40164-023-00469-0
|View full text |Cite
|
Sign up to set email alerts
|

The roles of tissue resident macrophages in health and cancer

Minmin Cao,
Zihao Wang,
Wanying Lan
et al.

Abstract: As integral components of the immune microenvironment, tissue resident macrophages (TRMs) represent a self-renewing and long-lived cell population that plays crucial roles in maintaining homeostasis, promoting tissue remodeling after damage, defending against inflammation and even orchestrating cancer progression. However, the exact functions and roles of TRMs in cancer are not yet well understood. TRMs exhibit either pro-tumorigenic or anti-tumorigenic effects by engaging in phagocytosis and secreting diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 255 publications
0
4
0
Order By: Relevance
“…Skin-resident macrophages can be classified into two main subtypes, i.e., Langerhans cells (LCs) of the epidermis and dermal macrophages [6]. Due to their mixed origin, LCs share the features of both macrophages and dendritic cells [7].…”
Section: Macrophages In the Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin-resident macrophages can be classified into two main subtypes, i.e., Langerhans cells (LCs) of the epidermis and dermal macrophages [6]. Due to their mixed origin, LCs share the features of both macrophages and dendritic cells [7].…”
Section: Macrophages In the Skinmentioning
confidence: 99%
“…Due to their mixed origin, LCs share the features of both macrophages and dendritic cells [7]. Therefore, they are capable of presenting antigens to T lymphocytes in the skin and draining lymph nodes [6]. At the immunological synapse, LC-derived signaling enables T cells to adapt the effector immune response to the type of antigenic stimulus [8].…”
Section: Macrophages In the Skinmentioning
confidence: 99%
“…AMs, together with the alveolar epithelium, play a central role in protecting against the outside environment and are closely linked to the alveolar epithelium. AMs are conjunct to alveolar epithelial cells and receive granulocyte–macrophage colony-stimulating factor (GM-CSF) from epithelial cells [ 8 , 15 ]. GM-CSF, encoded by the colony-stimulating factor 2 ( Csf2 ) gene, is necessary for the differentiation of fetal monocytes into AMs, and macrophages found in the airways of Csf2 knockout (KO) mice cannot fully differentiate into AMs [ 16 ].…”
Section: Main Textmentioning
confidence: 99%
“…These findings suggest that cancer tissues contain TRMs in addition to infiltrating macrophages or TAMs. However, although previous studies have reported the interactions between some TRMs and malignant tumors such as glioma, hepatocellular carcinoma, and metastatic cancer, the exact functions and roles of TRMs in cancer tissues are not fully understood [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%